Development of Marine and Coastal Tourism Based on Blue Economy - Dimas Tegar; Raja Oloan Saut Gurning (Institut Teknologi Sepuluh Nopember, 2018)
Marine and coastal tourism as one of the largest segments of the maritime economy sector, as well as the largest component of the tourism industry, often leads to controversy over environmental impact and compatibility with other human activities. The application of economic and tourism concepts that are oriented towards environmental conservation and natural resources is one option to overcome the problem. The Blue Economy concept offers an economic concept based on ecosystem principles, where the development will not only generate economic growth but also ensure ecological and social sustainability. In addition, the concept of ecotourism also offers a tourism activity that prioritizes aspects of nature conservation and improving the welfare of the community